3D printing of PVDF-based piezoelectric nanogenerator from programmable metamaterial design: Promising strategy for flexible electronic skin. (May 2023) - Pei, Haoran; Jing, Jingjing; Chen, Yinghong; Guo, Jiajun; Chen, Ning
Abstract: The high-performance piezoelectric nanogenerator (PENG) with good flexibility, tunability and sensitivity is desirable for the next-generation of wearable electronics. However, the 3D printing of unique architectures and arbitrary shapes could endow the conformal electronic sensors with excellent flexibility and functionality. In this work, the self-poled PENG were successfully fabricated by incorporating the oriented ionic salt-montmorillonite (IS-MMT) co-fillers into poly (vinylidene fluoride) (PVDF) matrix and then performing 3D printing. This hence could give the 3D printed PENG the locked interfacial piezoelectric polarization. More importantly, the self-adaptive conformal PENG based on auxetic metamaterial has also been developed, which is beyond the practicability of the traditional 2D PENG. The effect of various architectures of the metamaterial on the mechanical and piezoelectric responses was particularly discussed. The tailoring of the 3D printed cell with metamaterial of serpentine geometries shows the appealing advantages of high sensitivity to structure variation, thus being beneficial for easier regulation of piezoelectric output. When mounted on the joints as a wearable healthcare monitoring device, this 3D printed PENG could accurately detect the movement of muscles, demonstrating its potential in motion tracking and sign-language interpretation. Obviously, this work could provide a new idea for design and fabrication of programmable wearable electronics. Graphical Abstract: An innovative strategy of coupling 3D printing with a metamaterial design was proposed to construct the electronic skins based on the PENG with desirable flexibility, tunability and sensitivity. The PENGs were successfully fabricated by incorporating the oriented ionic salt-montmorillonite (IS-MMT) templates into poly(vinylidene fluoride) (PVDF) matrix, which could give the 3D printed PENG the locked interfacial piezoelectric polarization. ga1 Highlights: An innovative strategy of coupling 3D printing with a metamaterial design was proposed to construct the electronic skins. The self-poled PENGs were fabricated by incorporating the oriented ionic salt-montmorillonite templates into PVDF matrix. The tailoring of 3D printed metamaterial cell showed the appealing advantages of high sensitivity to structure variation. The 3D printed PENGs could demonstrate its great potential in motion tracking and sign-language interpretation.